Companion to European Heritage Revivals - Egberts, Linde; Koos Bosma (Springer Nature, 2014)
Cultural Heritage; Cultural Management; Heritage Strategies; Heritage Experience; Cultural Heritage Routes; Routes des Vins d'Alsace; Liberation Route Arnhem Nijmegen; Region Identity Battle Field